Ultrathin metal-mesh Janus membranes with nanostructure-enhanced hydrophobicity for high-efficiency fog harvesting. (20th August 2022) - Chen, Liyang; Li, Wei; Gan, Zhuofei; Zhou, Yaya; Chen, Ming; Cui, Dehu; Ge, Haixiong; Chan, Paddy K.L.; Wang, Liqiu; Li, Wen-Di
Abstract: Fog harvesting has been reckoned to be one of the most facile and economical approaches to alleviating the ever-increasing global water scarcity. Janus membranes, especially metallic ones, outperform other fog collectors in terms of fog harvesting efficiencies, and they are the selection for sustainable water production as passive devices. However, there is a lack of metallic Janus membranes with ultrasmall feature sizes due to the limitation of the laser ablation fabrication method, which restrains parameter optimization for highly efficient fog collectors. In this work, photolithography, electroplating, and nanoimprint lithography processes are employed to enable ultrasmall membrane thickness and nanopatterning on the membrane surface. A 4-μm-thick ultrathin hierarchical metal-mesh Janus membrane with a pitch of 60 μm is fabricated, which achieves a record-high water collection rate of 233 mg cm −2 ·min −1 with nanostructure-enhanced hydrophobicity. The morphology of the membrane is characterized by scanning electron microscopy, while the fog collection process is observed under a high-speed camera and a microscope. Experimental measurement and finite-element numerical modeling unveil that a smaller membrane thickness and a more hydrophobic water-collecting surface contribute to higher water collection rates by accelerating water transport and reducing water re-evaporation. Graphical abstract: Image 1 Highlights: Photolithography and electroplating replace laser ablation for metallic JM fabrication. Metallic JMs with unprecedented thickness down to 4 μm are fabricated. Nanopatterning on JMs changes surface wettability and boosts WCR. A record-high WCR of 233 mg cm −2 ·min −1 is achieved.